A unique case of hereditary bilateral segmental neurofibromatosis on the face Neurofibromatose segmentar bilateral hereditária da face: caso único - Irena Jankovic; Predrag Kovacevic; Milan Visnjic; Dimitrije Jankovic; Milena Velickovic (Sociedade Brasileira de Dermatologia, 2012)
Segmental neurofibromatosis is a rare clinical finding generally with no family history and facial involvement. There are four subtypes of segmental neurofibromatosis: true segmental, localized cases with deep involvement, hereditary segmental and bilateral segmental neurofibromatosis. Here we report three patients from the same family (father, son and granddaughter) with segmental bilateral neurofibromatosis on the face. This form hasn't noticed in the literature. A neurofibromatose segmentar é um achado clínico raro, geralmente com história familiar negativa e raro envolvimento facial. Existem quatro subtipos de neurofibromatose segmentar: segmentar verdadeira, segmentar com envolvimento visceral profundo, segmentar com história familiar e segmentar cutânea bilateral. Aqui nós reportamos três pacientes de uma mesma família (pai, filho e neta) com neurofibromatose segmentar bilateral na face. Esta forma ainda não foi relatada na literatura.